Molecular Patterns Discriminate Accommodation and Subclinical Antibody-mediated Rejection in Kidney Transplantation. Issue 5 (May 2019) - Hruba, Petra; Krejcik, Zdenek; Stranecky, Viktor; Maluskova, Jana; Slatinska, Janka; Gueler, Faikah; Gwinner, Wilfried; Bräsen, Jan Hinrich; Wohlfahrtova, Mariana; Parikova, Alena; Osickova, Klara; Fronek, Jiri; et al.
Abstract : Background: Accommodation in ABO-incompatible (ABOi) transplantation and subclinical antibody-mediated rejection in HLA-incompatible (HLAi) transplantation share several morphological similarities. Because the clinical long-term outcomes differ, we hypothesized different molecular processes involved in ABOi transplantation and subclinical antibody-mediated rejection. Methods: Using Illumina Human HT-12 v4 Expression BeadChips, the whole transcriptome was evaluated based on 3-month protocol C4d+ biopsies in otherwise stable ABOi and HLAi kidney grafts, as well as in C4d-negative HLA-compatible grafts exhibiting normal histological findings. Top differently regulated genes were further validated using real-time quantitative polymerase chain reaction in another patient cohort and complement regulatory proteins by immunohistochemistry. Results: In the case of genes involved in immune response–related biological processes, ABOi and HLAi cohorts had similar transcriptomic profiles to C4d-negative controls. The majority of deregulated genes in the ABOi and HLAi groups consisted of metallothioneins and epithelial transporter genes. Increased expression of epithelial transporters ( SLC4A1, SLC4A9, SLC17A3, SLC12A3, and SLC30A2 ) and class 1 metallothioneins ( MT1F, MT1G, and MT1X ) in HLAi transplantation was validated by real-time quantitative polymerase chain reaction. In comparison to controls, both incompatible cohorts were characterized by the upregulation of intrarenal complement regulatory genes. CD46 and CD59 transcripts were increased in the ABOi cohort, whereas CD46 solely in HLAi group, and CD59 protein expression was similar in both incompatible groups. Conclusions: Several epithelial transporters and metallothioneins discriminate subclinical antibody-mediated rejection in HLAi transplantation from accommodation in ABOi transplantation, which suggest different involved downstream mechanisms and increased risk of injury in HLAi settings. Metallothioneins with their antioxidative properties may help to attenuate the inflammation response induced by donor-specific anti-HLA antibody binding. Abstract : Supplemental Digital Content is available in the text.